Creatine Kinase and Mortality in Peritoneal Dialysis - Wu, Xianfeng; Zhou, Lei; Zhan, Xiaojiang; Wen, Yueqiang; Wang, Xiaoyang; Feng, Xiaoran; Wang, Niansong; Peng, Fenfen; Wu, Junnan (Frontiers in Cardiovascular Medicine, 2022)
Background: The association between serum creatine kinase and mortality in peritoneal dialysis (PD) patients remained unknown. Methods: We retrospectively collected data on 3446 incident PD patients from five PD centers in China between January 1, 2005, and May 31, 2020. Creatine kinase was collected one week before the start of PD. We examined the association between creatine kinase and mortality using Cox proportional hazards model. Results: The median creatine kinase was 113 (range, 1.22-4574) IU/L. With a median follow-up of 39.5 (range, 3.1-181.5) months, 763 (22.1%) all-cause deaths occurred, including 384 (11.1%) cardiovascular deaths. As compared with a creatine kinase of 111 to 179 IU/L (reference range), a higher creatine kinase (> 179 IU/L) was associated with increased risks of all-cause mortality (hazards ratio [HR], 1.72; 95% confidence interval [CI], 1.35 to 2.00; E-value = 2.83) and cardiovascular mortality (HR, 1.44; 95% CI, 1.05 to 1.98; E-value = 2.24). As compared with the reference range, a lower creatine kinase (< 111 IU/L) was associated with increased risks of all-cause mortality HR, 1.40; 95% CI, 1.12 to 1.76; E-value = 2.15) and cardiovascular mortality (HR, 1.45; 95% CI, 1.08 to 1.94; E-value = 2.26). Interaction between creatine kinase and no hyperlipidemia (p = 0.034 for interaction) was observed. Conclusions: A creatine kinase before the start of PD between 111 and 179 IU/L was associated with a lower risk of death than a higher or lower creatine kinase, resulting in a U-shaped association curve.